Cover Picture: Ruthenium‐Catalyzed Hydrogenation of Oxygen‐Functionalized Aromatic Compounds in Water (ChemCatChem 11/2013). Issue 11 (25th October 2013) - Jantke, Dominik; Cokoja, Mirza; Drees, Markus; Herrmann, Wolfgang A.; Kühn, Fritz E.
<x xml:space="preserve">Abstract</x> On the way to clean biomass conversion The cover picture shows that oxygen functionalized arenes serve as model substrates for aromatic derivatives found for example in lignocellulosic biomass such as phenol or acetophenone. These arenes are hydrogenated to obtain the analogue cyclohexane derivatives in water. As precatalyst, a highly soluble sulfonated ruthenium(II) bis‐carbene complex is used. In their Full Paper on page 3241 ff., W. A. Herrmann, F. E. Kühn and co‐workers explain that the results imply a homogenous reaction pathway involving the formation of a ruthenium(II) hydride complex as the active species.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>